2008
DOI: 10.1103/physrevlett.100.143001
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Retrieval of Target Structure Information from Laser-Induced Rescattered Photoelectron Momentum Distributions

Abstract: We have measured two-dimensional photoelectron momentum spectra of Ne, Ar, and Xe generated by 800-nm, 100-fs laser pulses and succeeded in identifying the spectral ridge region (back-rescattered ridges) which marks the location of the returning electrons that have been backscattered at their maximum kinetic energies. We demonstrate that the structural information, in particular the differential elastic scattering cross sections of the target ion by free electrons, can be accurately extracted from the intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
107
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(108 citation statements)
references
References 27 publications
1
107
0
Order By: Relevance
“…2 we plotted LES-energy positions scaled by the ponderomotive energy, p 2 LES (n)/2U p , with solid lines to compare with experiment. Note, that the corrections due to the potential δp and focus averaging C av reduce the LES position in energy by about 25 % compared to the "pure" result (6). The product form (10) restores the universal pulse duration dependenceζ(n) of the LES and shows how the laser parameters and the binding energy of the electron influence the LES.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 we plotted LES-energy positions scaled by the ponderomotive energy, p 2 LES (n)/2U p , with solid lines to compare with experiment. Note, that the corrections due to the potential δp and focus averaging C av reduce the LES position in energy by about 25 % compared to the "pure" result (6). The product form (10) restores the universal pulse duration dependenceζ(n) of the LES and shows how the laser parameters and the binding energy of the electron influence the LES.…”
mentioning
confidence: 99%
“…A lot of attention has been devoted to these phenomena since their understanding via a three-step model involving simple classical trajectories in the strong laser field [2,3], succeeded to describe such processes (for example their high-energy cutoff [4,5]). More recently, the concept of strong field "quasi-free" motion of a high-energy rescattering electron was even used for laser-induced electron diffraction [6][7][8][9].…”
mentioning
confidence: 99%
“…Apart from the more traditional approaches based on x-ray diffraction [2,6] and ultrafast electron diffraction (UED) [7], methods based on the recollision phenomena with intense driving lasers have been proposed and successfully tested on simple molecules. We mention here high-order harmonic-generation (HHG) spectroscopy [8][9][10][11][12] and laser-induced electron diffraction (LIED) [9,[13][14][15][16][17][18]. Time-resolved photoelectron spectroscopy (TRPES) and time-resolved molecular-frame photoelectron angular distribution (TRMFPAD) measurements proposed recently [19,20] are capable of imaging valence-electron dynamics and atom motion during a chemical reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Combining conventional electron or X-ray beam methods with femtosecond laser pulses provides improved temporal resolutions for molecular dynamics investigation approaching atomic time scales [23][24][25][26] . However, recent experiments [27][28][29][30][31] demonstrated that intense, isolated femtosecond pulses alone are sufficient for imaging simple molecules via a strong-field three-step process 32,33 (see Supplementary Discussion). First, the intense, low-frequency laser ionizes the molecule.…”
mentioning
confidence: 99%
“…Conceptually this is analogous to the external electron beam used in conventional electron diffraction (CED) studies. Dubbed laser-induced electron diffraction (LIED) 34,35 , the method relies on extracting elastic differential cross-sections (DCS) from the two-dimensional (2D) photoelectron angular distributions [27][28][29][30][31] . Recently, picometre and femtosecond resolutions were demonstrated for N 2 and O 2 bond distance determination by fitting the extracted angledependent elastic DCS 36 .…”
mentioning
confidence: 99%